The effect of CPP-ACP containing fluoride on Streptococcus mutans adhesion and enamel roughness - Yulita Kristanti; Widya Asmara; Siti Sunarintyas; Juni Handajani (Dental Journal (Majalah Kedokteran Gigi), 2013)
Background: Direct contact between the bleaching agent and the enamel surface results in demineralization, alteration in surface roughness and bacterial adhesion. Many studies try to minimize this side effect through different way. Purpose: The aim of this study was to determined the effect of Calcium Phospho Peptide-Amorphous Calcium Phosphate (CPP-ACP) containing fluoride application before and after bleaching procedure on the adhesion of S. Mutans and enamel roughness. Methods: The samples were 6 teeth which were divided into 4 groups, and each tooth was cut into four pieces. Group A and C were treated with CPP-ACP after bleaching, while group B and D were treated with CPP-ACP before and after bleaching. CPP-ACP used in group C and D was the one that contain fluoride. After treatment, all samples were sterilized, immersed in steril human saliva for one hour, then immersed into S. mutans suspension of 108 CFU. Samples were incubated overnight. On the next day the samples were put into steril BHI and vortexed for one minute to detach the bacteria. Fifteen ml BHI containing bacteria was poured into TYS agar then incubated 37°Cfor 48 hours. Bacterial colony was counted with colony counter. The SEM examination was done on all samples. Results: Application of desensitizing agent reduced the S.mutans adhesion significantly among groups (p<0.05) except between group A and C. SEM evaluation revealed significant differences among groups. Conclusion: The application of CPP-ACP containing fluoride before and after bleaching was effective to reduce the accumulation of S.mutans colony and enamel roughness.Latar belakang: Kontak langsung antara bahan bleaching dan permukaan enamel menyebabkan demineralisasi, perubahan kekasaran permukaan dan berpengaruh terhadap banyaknya bakteri Streptococcus mutans (S. mutans) yang melekat. Banyak peneliti mencoba meminimalkan efek samping ini dengan cara yang beragam. Tujuan: Penelitian ini bertujuan untuk meneliti efek aplikasi CPP-ACP mengandung fluor sebelum dan setelah bleaching terhadap adhesi S.mutans dan kekasaran enamel. Metode: Sampel penelitian adalah 6 buah gigi yang dibagi dalam 4 kelompok, kemudian masing-masing gigi dibelah menjadi 4 bagian. Kelompok A dan C diaplikasi dengan CPP-ACP setelah bleaching, sedang Kelompok B dan D diaplikasi CPP-ACP sebelum dan setelah bleaching. CPP-ACP yang digunakan pada kelompok C dan D adalah yang mengandung fluor. Setelah perlakuan, semua sampel disterilkan dan direndam dalam saliva steril, lalu direndam dalam suspensi S. mutans 108 CFU dan diinkubasi 24 jam. Hari berikutnya sampel dimasukkan dalam BHI steril, divortex 1 menit untuk melepaskan bakteri. Lima belas ml BHI yang berisi S. mutans tersebut diambil untuk dikultur dalam agar TYS dan diinkubasi 37°C selama 48 jam. Bakteri yang tumbuh dihitung dengan colony counter. Pemeriksaan SEM dilakukan untuk meneliti permukaan enamel. Hasil: Aplikasi CPP-ACP(F) menurunkan jumlah bakteri yang melekat pada enamel secara signifikan (p<0,05) pada semua kelompok, kecuali antara kelompok A dan C. Simpulan: Aplikasi CPP-ACP mengandung fluor sebelum dan sesudah bleaching efektif mengurangi akumulasi S. mutans dan kekasaran pada permukaan enamel.